2014
DOI: 10.1111/bdi.12271
|View full text |Cite
|
Sign up to set email alerts
|

International Society for Bipolar Disorders Task Force on Suicide: meta‐analyses and meta‐regression of correlates of suicide attempts and suicide deaths in bipolar disorder

Abstract: This paper reports on the presence and magnitude of the correlates of suicide attempts and suicide deaths in bipolar disorder. These findings do not address causation, and the heterogeneity of data sources should limit the direct clinical ranking of correlates. Our results nonetheless support the notion of incorporating diagnosis-specific data in the development of models of understanding suicide in bipolar disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
200
5
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 285 publications
(220 citation statements)
references
References 97 publications
13
200
5
2
Order By: Relevance
“…Consistent with this idea, a Danish case-register study found that the risk of dementia in bipolar disorder increased with the number of affective episodes (Kessing and Andersen, 2004), and was less marked among patients receiving continuous treatment with lithium (but not with other mood stabilizers) (Kessing et al, 2010). Bipolar disorder has also been associated with increased mortality (Almeida et al, 2014), including death by suicide (Schaffer et al, 2015). A systematic review and meta-analysis of 31 studies that included over 300,000 people with bipolar disorder found that the condition more than doubled the risk of premature death both from natural and non-natural causes (such as suicide or accidents) (Hayes et al, 2015).…”
Section: Cognitive Function In Bipolar Disorder and The Risk Of Demementioning
confidence: 92%
“…Consistent with this idea, a Danish case-register study found that the risk of dementia in bipolar disorder increased with the number of affective episodes (Kessing and Andersen, 2004), and was less marked among patients receiving continuous treatment with lithium (but not with other mood stabilizers) (Kessing et al, 2010). Bipolar disorder has also been associated with increased mortality (Almeida et al, 2014), including death by suicide (Schaffer et al, 2015). A systematic review and meta-analysis of 31 studies that included over 300,000 people with bipolar disorder found that the condition more than doubled the risk of premature death both from natural and non-natural causes (such as suicide or accidents) (Hayes et al, 2015).…”
Section: Cognitive Function In Bipolar Disorder and The Risk Of Demementioning
confidence: 92%
“…Such delay is particularly ominous given the very high rate of suicide among both type I and type II bipolar disorder patients (ca. 0.36%/year, with a male:female ratio of approximately 1.6 [0.44/0.28]), with standardized mortality ratios (SMRs) estimated at over 20 times above rates in the general population (0.36/0.015=24) (21)(22)(23)(24)(25). In addition, ratios of attempts/suicides (A/S) are much lower in bipolar disorder than in the general population, reflecting greater lethality of methods and intent (25,26).…”
mentioning
confidence: 99%
“…0.36%/year, with a male:female ratio of approximately 1.6 [0.44/0.28]), with standardized mortality ratios (SMRs) estimated at over 20 times above rates in the general population (0.36/0.015=24) (21)(22)(23)(24)(25). In addition, ratios of attempts/suicides (A/S) are much lower in bipolar disorder than in the general population, reflecting greater lethality of methods and intent (25,26). Mortality also is increased in bipolar disorder owing to moderately elevated SMRs (2-3-fold) for co-occurring common general medical disorders in older bipolar disorder patients (27,28).…”
mentioning
confidence: 99%
See 2 more Smart Citations